Prevalence of TT virus in a CAPD population - KOÇ, MEHMET (KARGER, 2002)
TT virus (TTV) has recently been identified in patients with post-transfusion non-A, non-G hepatitis. It is reported to be common in patients with a variety of liver diseases and with history of transfusion. Its pathogenesis in chronic liver diseases remains unclear. In this study, we have determined the prevalence of TTV in a continuous ambulatory peritoneal dialysis (CAPD) population and related its prevalence with history of previous hemodialysis, transfusion, HCV positivity and serum alanine amino-transferase (ALT) levels. TTV was detected in 44% of 63 CAPD patients and 30% of 43 healthy controls (p = 0.15). Frequency of TTV was similar in previously hemodialysed and never hemodialysed (8/14, 57% vs. 20/40, 41%, p =0.15) and previously transfused and non-transfused (7/19, 37% vs. 15/44, 34%) CAPD patients. Prevalence of TTV was also similar in HCV(+) and HCV(-) patients. Serum ALT levels were 19 16 and 20 12 ILIA in TTV(+) and TTV(-) patients, respectively. These results indicate that prevalence of TTV in a CAPD population is similar to healthy controls, and other routes of transmission in addition to parenteral routes might be involved in the transmission of TTV. Copyright (C) 2002 S. KargerAG, Basel.
Keywords: TT virus; CAPD; hepatitis; transfusion; hemodialysis; POSTTRANSFUSION HEPATITIS; BLOOD-DONORS; INFECTION; DNA